2001
DOI: 10.1063/1.1376398
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization phenomena in nephron–nephron interaction

Abstract: Experimental data for tubular pressure oscillations in rat kidneys are analyzed in order to examine the different types of synchronization that can arise between neighboring functional units. For rats with normal blood pressure, the individual unit ͑the nephron͒ typically exhibits regular oscillations in its tubular pressure and flow variations. For such rats, both in-phase and antiphase synchronization can be demonstrated in the experimental data. For spontaneously hypertensive rats, where the pressure variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 24 publications
1
45
0
2
Order By: Relevance
“…2͑a͒, are the same as have been reported previously. 5,14,19,25 The tubule pressure and the arteriolar diameter oscillate, and the motion on the phase plane is that of a limit cycle oscillator. Parameters have been chosen that are typical of measurements made in normal animals.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2͑a͒, are the same as have been reported previously. 5,14,19,25 The tubule pressure and the arteriolar diameter oscillate, and the motion on the phase plane is that of a limit cycle oscillator. Parameters have been chosen that are typical of measurements made in normal animals.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The model has been described and evaluated in detail in other studies, 5,14,19,20,25 and is presented unmodified in the Appendix. The model consists of a set of five coupled ordinary differential equations.…”
Section: B Nephron Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaotic phase synchronization has been observed in a broad range of different physical, technical and biological systems, including a plasma discharge tube paced with a low amplitude wave generator [8], an array of coupled electronic oscillators [9], and a pair of interacting functional units of the kidney [10]. The transition between phase-locked and un-locked states represents a signi¿cant change in behavior, and we have previously suggested that transitions between different synchronization states among oscillatory biological processes may represent an important component in the normal physiological regulation of the living organism [10].…”
Section: Introductionmentioning
confidence: 99%
“…The transition between phase-locked and un-locked states represents a signi¿cant change in behavior, and we have previously suggested that transitions between different synchronization states among oscillatory biological processes may represent an important component in the normal physiological regulation of the living organism [10].…”
Section: Introductionmentioning
confidence: 99%